Intraspecific Facilitation Through Host Plant Quality Improvement? Observations on the Aggregation Behaviour and Population Biology of the Senescence Inducing Phloem Feeder (Ischnodemus Sabuleti) - Gidó, Zsolt; Lehoczky, Éva (Journal of Central European Green Innovation, 2023)
The aggregation behaviour and the senescence inducing effect on its host plants (Glyceria spp.) of the European chinch bug (Ischnodemus sabuleti) is documented in several Hungarian high- density populations. The hypothesis of intraspecific facilitation through host plant quality improvement is formulated and discussed in detail. We suggest that drought stressed host plants improve the performance of I. sabuleti and facilitate the local population outbreaks. We suggest that the optimal host plant drought stress level is higher for senescence feeding herbivores than for the flush feeding herbivores.
Keywords: Ischnodemus sabuleti; Heteroptera; Blissidae; Glyceria maxima; intraspecific facilitation; aggregation behaviour